Collagenous and elastotic marginal plaques of the hand: A potential clue to the diagnosis of alkaptonuria. (5th November 2018) - Good, Allison J.; Snodgrass, Alexandra L.; De Benedetto, Anna; Motaparthi, Kiran
Abstract : Collagenous and elastotic marginal plaques of the hand (CEMPH) is a rare, chronic keratoderma characterized by hyperkeratotic linear plaques located along the radial and ulnar aspects of the hands bilaterally. As an isolated finding, CEMPH occurs secondarily to chronic trauma and photodamage. Herein, CEMPH is described as a manifestation of alkaptonuria (AKU). In addition to keloidal collagen, ochronotic fibers and fragmented, thickened elastic fibers were observed. Additionally, mucin deposition—not previously described in this clinical context—was also identified. Given their overlapping clinicopathologic features, CEMPH due to AKU should be distinguished from the acquired variant as well as acrokeratoelastoidosis.